MUSLIM PERSONALITY MOTIVATION AND RELIGIOUS ATTITUDE (CASE STUDY: ANALYSIS OF ISLAMIC EDUCATIONAL PSYCHOLOGY PERSPECTIVE) - Selasni, Ismi; Aminullah (Qawwam : The Leader's Writing, 2024)
This literature review article aims to review the relationship between religious motivation, the formation of Muslim personality, and religious attitudes, and their implications in Islamic education. Muslim personality is formed through the internalization of Islamic values influenced by intrinsic and extrinsic motivation, and supported by religious education and the environment. Religious motivation is the main driver for individuals to practice Islamic teachings consistently, which ultimately affects the quality of personality. Religious attitudes reflect the depth of internalization of religious values and are manifested in daily behavior. This study found that the implementation of motivation, the formation of Muslim personality, and religious attitudes in Islamic education aims to produce a generation with noble character through the methods of exemplary behavior, habituation, and targhib and tarhib. A conducive educational environment plays an important role in fostering students' motivation and religious attitudes.